Cardioprotective effect of lipstatin derivative orlistat on normotensive rats submitted to cardiac ischemia and reperfusion - Menezes-Rodrigues,Francisco Sandro (2018)
Abstract Purpose: To evaluate in vivo animal model of cardiac ischemia/reperfusion the cardioprotective activity of pancreatic lipase inhibitor of the orlistat. Methods: Adult male Wistar rats were anesthetized, placed on mechanical ventilation and underwent surgery to induce cardiac I/R by obstructing left descending coronary artery followed by reperfusion to evaluation of ventricular arrhythmias (VA), atrioventricular block (AVB) and lethality (LET) with pancreatic lipase inhibitor orlistat (ORL). At the end of reperfusion, blood samples were collected for determination of triglycerides (TG), very low-density lipoprotein (VLDL), low-density lipoprotein (LDL), high-density lipoprotein (HDL), lactate dehydrogenase (LDH), creatine kinase (CK), and creatine kinase-MB (CK-MB). Results: Treatment with ORL has been able to decrease the incidence of VA, AVB and LET. Besides that, treatment with ORL reduced serum concentrations of CK and LDL, but did not alter the levels of serum concentration of TG, VLDL and HDL. Conclusion: The reduction of ventricular arrhythmias, atrioventricular block, and lethality and serum levels of creatine kinase produced by treatment with orlistat in animal model of cardiac isquemia/reperfusion injury suggest that ORL could be used as an efficient cardioprotective therapeutic strategy to attenuate myocardial damage related to acute myocardial infarction.